2022
DOI: 10.3390/ijms232315083
|View full text |Cite
|
Sign up to set email alerts
|

Selective Silencing of Disease-Associated B Lymphocytes from Hashimoto’s Thyroiditis Patients by Chimeric Protein Molecules

Abstract: Hashimoto’s thyroiditis is one of the most common endocrine disorders, affecting up to 20% of the adult population. No treatment or prevention exists except hormonal substitution for hypothyroidism. We hypothesize that it may be possible to selectively suppress anti-thyroglobulin (Tg) IgG antibody-producing B lymphocytes from HT patients by a chimeric protein molecule containing a monoclonal antibody specific for the human inhibitory receptor CR1, coupled to peptide epitopes derived from Tg protein. We expect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…When discussing the importance of B lymphocytes, attention should also be paid to the influence of CD4+ T lymphocytes on their activity. It has been shown that, after binding to TG epitopes, they influence the process whereby B lymphocytes are differentiated into plasma cells [41]. Observations confirm the presence of B lymphocytes in the thyroid gland and their involvement in the development of the disease.…”
Section: B Lymphocytesmentioning
confidence: 63%
See 3 more Smart Citations
“…When discussing the importance of B lymphocytes, attention should also be paid to the influence of CD4+ T lymphocytes on their activity. It has been shown that, after binding to TG epitopes, they influence the process whereby B lymphocytes are differentiated into plasma cells [41]. Observations confirm the presence of B lymphocytes in the thyroid gland and their involvement in the development of the disease.…”
Section: B Lymphocytesmentioning
confidence: 63%
“…Observations confirm the presence of B lymphocytes in the thyroid gland and their involvement in the development of the disease. Patients with autoimmune thyroid diseases, including Hashimoto's thyroiditis, have also been observed to have reduced numbers in anergic TG-specific B cells in the blood [41]. Similar results were obtained in a study conducted by Smith et al, where a decreased total number of anergic B cells and those capable of reacting with TG and TPO, as well as higher levels of antibodies against self-antigens, were found in the blood of newly diagnosed patients compared to those with a longer history of the disease or those without the disease [40].…”
Section: B Lymphocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to this, specific antibodies conjugated with peptides may be used as therapeutics as well. In a study by Ralchev and coworkers, chimeric protein molecules composed of synthetic peptides coupled to a monoclonal antibody were able to inhibit B-cell-specific differentiation to plasmablasts and promote the apoptosis of targeted cells, each of which could aid in the treatment of Hashimoto Thyroiditis [12].…”
mentioning
confidence: 99%